Breaking the Cycle: Reforming Indonesia’s Justice System to Prioritize Victim-Centered Solutions - Amriyanto Amriyanto; Husen Alting; Handar Subhandi Bakhtiar; Grahadi Purna Putra (Jurnal Dinamika Hukum, 2024)
The article attempts to look at the location and role of victims of crime in the criminal justice system and how the system is manipulated to corner the victims and offer solutions to the victims' problems. The Indonesian criminal justice system places the position of criminal victims as no more than those who assist law enforcement in uncovering crimes. The obstacle that the victim encounters in the criminal justice system is that the victim is only used as an object of evidence alone, not to mention if there is a blacklash from the perpetrator to the perpetrator who goes to jail only for penance. The application of restorative justice is one of the best solutions to how the criminal justice system is run. Involving victims and perpetrators and their families in a balanced and fair way as well as meeting the needs of the victims adapted to the perpetrators' ability to be responsible reflects the kinship character of the kinship culture of the Indonesian people.